2018
DOI: 10.1016/j.ijppaw.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The wild world of Guinea Worms: A review of the genus Dracunculus in wildlife

Abstract: Nematodes are an extremely diverse and speciose group of parasites. Adult dracunculoid nematodes (Superfamily Dracunculoidea) occur in the tissues and serous cavities of mammals, fish, reptiles, amphibians and birds. Of the dracunculid group, perhaps best known is Dracunculus medinensis, the human Guinea Worm. Considerable work has been done on D. medinensis; however recent infections in peri-domestic dogs and the finding of naturally-infected paratenic hosts (previously unreported for D. medinensis) indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 68 publications
(167 reference statements)
1
30
0
Order By: Relevance
“…Dracunculus infections have been documented in a variety of hosts from multiple regions of North America; however, identification in most studies was limited to the morphology of female worms, which cannot be reliably identified to species without genetic characterization. Although male worms are morphologically distinguishable, they are rarely detected (Cleveland et al, 2018). The only previous study that examined the host range of D. insignis (confirmed by sequence analysis) was conducted in Canada and found that D. insignis recovered from raccoons, mink, fishers (Martes pennanti), and river otters had minimal sequence divergence among hosts, supporting the hypothesis that D. insignis is a host generalist (Elsasser et al, 2009).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Dracunculus infections have been documented in a variety of hosts from multiple regions of North America; however, identification in most studies was limited to the morphology of female worms, which cannot be reliably identified to species without genetic characterization. Although male worms are morphologically distinguishable, they are rarely detected (Cleveland et al, 2018). The only previous study that examined the host range of D. insignis (confirmed by sequence analysis) was conducted in Canada and found that D. insignis recovered from raccoons, mink, fishers (Martes pennanti), and river otters had minimal sequence divergence among hosts, supporting the hypothesis that D. insignis is a host generalist (Elsasser et al, 2009).…”
mentioning
confidence: 70%
“…Dracunculus insignis has been well documented in raccoons across a wide geographic area of North America Beverly-Burton, 1974, 1977;Cleveland et al, 2018); however, detailed investigation into the range of susceptible wildlife, associated phylogenetic relationships, and the role of paratenic and transport hosts in the transmission cycle at endemic locations had yet to be investigated. Our study supports the role of raccoons as the most common definitive host for D. insignis (Crichton and Beverly-Burton, 1974) but also indicates the potential involvement of opossums in supporting sylvatic transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If numbers of copepods ingested under natural conditions is similar to our experimental data, numerous drinking events from contaminated water bodies may be necessary for Dracunculus transmission to occur. It is important to note the prevalence of infected copepods in a contaminated pond is poorly understood but is presumed to be relatively low based on past studies (range of 0.5-33.3%, average of 5.2%) [15][16][17] . Also, because both a female and male worm are required to complete the life cycle, and copepods infected with more than one Dracunculus L3 are likely to die 18 , multiple infected copepods must be ingested.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, despite our small sample size, our data indicate that dogs can ingest relatively few copepods while drinking, but there are still many factors to investigate to determine the primary transmission route(s) of D. medinensis in the remaining GWD-endemic countries. Other possibilities include ingestion of amphibian paratenic hosts or fish transport hosts 2,[4][5][6]15 . Currently, there are many interventions in place to minimize transmission risk including: tethering of infected dogs, treatment of potentially contaminated water bodies with Abate ® , and the burning or burial of fish entrails, but dog infections continue to occur suggesting that improved adherence to interventions or new interventions are necessary to interrupt transmission.…”
Section: Discussionmentioning
confidence: 99%